Baicalein Attenuates Pyroptosis and Endoplasmic Reticulum Stress Following Spinal Cord Ischemia-Reperfusion Injury via Autophagy Enhancement - Wu, Chenyu; Xu, Hui; Li, Jiafeng; Hu, Xinli; Wang, Xingyu; Huang, Yijia; Li, Yao; Sheng, Sunren; Wang, Yongli; Xu, Huazi; Ni, Wenfei; Zhou, Kailiang (Frontiers in Pharmacology, 2020)
Background: Spinal cord ischemia-reperfusion injury (SCIRI) is the main complication after the repair of a complex thoracoabdominal aortic aneurysm. Many clinical treatments are not ideal due to the complex pathophysiological process of this injury. Baicalein (BA), a component derived from the roots of the herb Scutellaria baicalensis, may contribute to the successful treatment of ischemia / reperfusion injury. Purpose: In the present study, the effects of BA on spinal cord ischemia-reperfusion injury and the underlying mechanisms were assessed. Materials and methods: Spinal cord ischemia was induced in C57BL/6 mice by blocking the aortic arch. Fifty-five mice were then randomly divided into four groups: Sham, SCIR+Vehicle, SCIR+BA, and SCIR+BA +3MA groups. At 0 and 24 hours pre-SCIRI and at 24 hours and 7 days post-SCIRI, evaluations with the Basso mouse scale (BMS) were performed. On postoperative 24 hours, the spinal cord was harvested to assess pyroptosis, endoplasmic reticulum stress mediated apoptosis and autophagy. Results: BA enhanced the functional recovery of spinal cord ischemia-reperfusion injury. In addition, BA attenuated pyroptosis, alleviated endoplasmic reticulum stress-mediated apoptosis, and activated autophagy. However, the effects of BA on the functional recovery of SCIRI, pyroptosis and endoplasmic reticulum stress-mediated apoptosis were reversed by the inhibition of autophagy. Conclusions: In general, our findings revealed that BA enhances the functional recovery of spinal cord ischemia-reperfusion injury by dampening pyroptosis and alleviating endoplasmic reticulum stress-mediated apoptosis, which are mediated by the activation of autophagy.